Music as a Therapeutic Tool - Virant, Jerca (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter examines the role of music as a therapeutic tool in educational and healthcare settings, emphasizing its positive impact on cognitive and emotional development as well as mental health. It underscores the importance of training teachers in music therapy to support not only students with disabilities but also the wider student population. Educators with appropriate competencies and skills can contribute to improving students' emotional abilities and academic performance. The chapter explores the benefits of implementing music programmes for therapeutic purposes and their impact on individuals. It also highlights the need for further, more extensive research into the use of music as a therapeutic tool in both health and education, given the demonstrated potential for improving mental health, reducing stress and anxiety, and enhancing overall well-being.